Exacerbation of visual hallucinations in Charles Bonnet syndrome due to the social implications of COVID-19 - Mariya Moosajee; Lee Jones; Lara Ditzel-Finn; Judith Potts (BMJ Open Ophthalmology)
Objective Charles Bonnet syndrome (CBS) occurs secondary to sight loss, characterised by spontaneous visual hallucinations. Symptom manifestation can be influenced by social isolation. This research aims to evaluate the effect of the COVID-19 pandemic lockdown on patients with CBS.Methods and analysis A prospective cross-sectional survey of 45 individuals with active CBS. Open and closed ended questions were used to measure patient-reported features of hallucinatory experiences during the COVID-19 lockdown and perceived episode triggers. Analysis comprised of descriptive statistics, analysis of variance and associations, supplemented with qualitative descriptions.Results The survey was operational for 31 days during the COVID-19 pandemic (June–July 2020). The mean (±SD) age of respondents was 69.3 (±18) years and the majority (42.2%) had macular disease. Loneliness during the lockdown was associated with changes in the nature of visual hallucinations (p=0.04). Individuals experiencing greater loneliness were, on average, older than those with no changes to their feelings of loneliness (mean age 73.3±17 vs 60.2±19 years; p=0.03). Despite experiencing greater feelings of loneliness (67%), most individuals (60%) had not accessed support services for this reason.Conclusions Around half of respondents in this survey experienced exacerbation of visual hallucinations during the COVID-19 pandemic, which may partly be explained by loneliness and/or environmental triggers. We provide suggestions to promote effective patient self-management of symptoms.